Family and Eco-citizenship - Lefebvre, Béatrice; Blanchet-Cohen, Natasha; Léger, Michel T. (Enfances, Familles, Générations, 2023)
Research framework:  Although the family is typically the place where socialization and learning begin, and where values, practices and cultures are handed down, the ways in which eco-citizenship is taught within the family remain underexplored in current research.Objectives: This introductory article, along with the other articles in this special issue, explores various aspects of the relationship between family and eco-citizenship.Methodology:  This article is based on a partial review of the humanities and social sciences literature on the subject.Results:  The introductory article and the texts that make up the special issue shed light on the ways in which family dynamics are changing, on children's and young people's involvement in environmental action, and on the role of institutions in the development of eco-citizenship.Conclusion: The social processes by which eco-citizenship is constructed, and the transformations that take place within families in response to eco-citizen actions, underline the need for practices and lifestyle changes that involve a diverse array of actors, including young people, their families, institutional bodies and policymakers. The scientific community needs to pay more attention to this issue, as literature on the subject is still scarce.Contribution: In addition to providing some insights into the relationship between the family and eco-citizenship, this article suggests avenues for research in cultural and international contexts, issues of social and environmental justice, and the roles played by media and digital technology in fostering eco-citizenship.